DAYA SAING UDANG SEGAR DAN UDANG BEKU INDONESIA DI NEGARA TUJUAN EKSPOR UTAMA - Ulfira Ashari; Sahara Sahara; Sri Hartoyo (School of Business, Bogor Agricultural University (SB-IPB), 2016)
Fishery is one of the sub-sectors holding role in the national economy. Fresh and frozen shrimps are the superior fishery export commodities contributing to Indonesia as the shrimp exporting country. Nevertheless, the volume of shrimp exports in Indonesia is still relatively low compared to that of other exporting countries. This is due to low productivity of shrimp farming in Indonesia. This study aimed to analyze the competitiveness of Indonesian fresh and frozen shrimps in the main export destination countries as well as to analyze the factors influencing the competitiveness in those countries. The data used in this study were series of timeline for 120 months, from January 2005 to December 2014. Thus, the analysis of the competitiveness of Indonesian shrimps was conducted by using Revealed Comparative Advantage (RCA), while the analysis of the factors influencing competitiveness of Indonesia shrimps was performed by using the Error Correction Model (ECM). The results showed that the competitiveness of fresh shrimps of Indonesia in its export destination countries is still low compared that of frozen shrimps. One of the factors affecting the competitiveness of fresh shrimp exports from Indonesia to Malaysia in the short term is its total production. The competitiveness of Indonesia frozen shrimps in the United States is influenced by the level of competitiveness of the frozen shrimp exports to America on the previous period, export prices of Vietnamese frozen shrimps, and frozen shrimp production in Indonesia.Keywords: competitiveness, fresh shrimps, frozen shrimps, RCA